The study on contamination of bottom sediments from the Odra River estuary (SW Baltic Sea) by tributyltin using environmetric methods. (December 2022) - Kucharski, Dawid; Giebułtowicz, Joanna; Drobniewska, Agata; Nałęcz-Jawecki, Grzegorz; Skowronek, Artur; Strzelecka, Agnieszka; Mianowicz, Kamila; Drzewicz, Przemysław
Abstract: We present the first comprehensive study on the occurrence of tributyltin (TBT) in the Odra River estuary (SW Baltic Sea) that encompasses both densely populated and urbanized agglomeration Szczecin city, and sparsely populated biosphere reserves "Natura 2000". Relationship between TBT and physicochemical parameters of bottom sediments such as granulometry total organic carbon (TOC), total nitrogen (TN), acid volatile sulfide (AVS), As, and metals: Ba, Cd, Co, Cr, Cu, Fe, Hg, Ni, Mn, Mo, Pb, Sn, and Zn was investigated in 120 samples collected in 2017 and 2018. The highest TBT concentrations were over 3000 ng g −1 (dry weight). They were observed in samples collected in the vicinity of the ship maintenance zones of the Szczecin city. Despite the EU ban on its use since 2003, TBT is still present in the environment. Environmetrics analyses such as correlation, cluster, and principal component analysis of obtained results revealed that the main source of sediments contamination by TBT, metalloids, and metals is likely related to the maritime industry: shipyards, ship maintenance as well as ports and marines. TBT is still present in the bottom sediments because of its emission to the environment with dust and paint chips formed during sandblasting cleaning of ship surfaces. The pollutant is further transported with water current to remote localization in the Szczecin Lagoon. Slow water exchange between the Szczecin Lagoon and the Baltic Sea favors accumulation of pollutants in the lagoon sediments. Therefore, it is necessary to implement environmentally friendly methods into ship maintenance and management of the materials from dredged waterways, harbors, and marinas. Graphical abstract: Image 1 Highlights: Tributyltin (TBT) is still emitted to the environment despite the EU ban on its use since 2003. Shipbuilding and maintenance zones are the main sources of TBT contamination. Sediments are the repository of TBT and heavy metals contamination in the environment. The dredged sediments from waterways and harbors may pose an environmental risk.